Absorption Enhancement of Thin Film Solar Cell Utilizing a Graphene-Based Metasurface - Amir Mehrpanah; Hassan Rasooli Saghai; Babak Sakkaki; Ali Daghigh (Journal of Optoelectronical Nanostructures)
Thanks to the unique features of graphene, graphene-based metasurfaces have gained great attention in electronic applications. This manuscript introduces a graphene-based metasurface aiming absorption enhancement in thin film solar cells. We manipulate our design to induce the plasmonic effect in our metasurface. We optimize our metasurface with 2D-GNRs on the top of a SiO2 layer with a thickness of 60 nm. A thin film solar cell (TFSC) is designed based on Si utilizing 2D-GNRs/SiO2 nanostructure and its characteristics are compured with and without 2D GNRs utilizing the FDTD method. The optical short circuit current density increases from 10.66 mA/cm2  to 19.07 mA/cm2  and solar generation rate increases from   to  with 2D GNRs on the top of SiO2.The plasmonic resonance peaks are reported at the wavelength of 567 nm and 680 nm. To minimize the transmission from TFSC and based on the transmission profile and solar generation rate, we propose Al as a reasonable and suitable choice for the bottom electrode.